2006
DOI: 10.1113/jphysiol.2006.117069
|View full text |Cite
|
Sign up to set email alerts
|

The ventral tegmental area revisited: is there an electrophysiological marker for dopaminergic neurons?

Abstract: The ventral tegmental area (VTA) and in particular VTA dopamine (DA) neurons are postulated to play a central role in reward, motivation and drug addiction. However, most evidence implicating VTA DA neurons in these functions is based on indirect electrophysiological characterization, rather than cytochemical identification. These physiological criteria were first established in the substantia nigra pars compacta (SNc), but their validity in the VTA is uncertain. In the current study we found that while 88 ± 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
508
7
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 461 publications
(572 citation statements)
references
References 71 publications
51
508
7
1
Order By: Relevance
“…Dopamine did not inhibit the firing of these classically defined non-dopaminergic or GABAergic neurons (Grace & Onn, 1989;Johnson & North, 1992). A recent study confirmed that almost all electrophysiologically-classified dopaminergic neurons are tyrosine hydroxylasepositive (Brown et al, 2009), despite discrepancies found in some other studies (Margolis et al, 2006;Margolis et al, 2010). "Dopamine neurones" referred to in this study are therefore those that conform to electrophysiological and pharmacological criteria, but not necessarily to the content of dopamine.…”
Section: Vta Slice Preparation and Electrophysiological Recordingssupporting
confidence: 73%
“…Dopamine did not inhibit the firing of these classically defined non-dopaminergic or GABAergic neurons (Grace & Onn, 1989;Johnson & North, 1992). A recent study confirmed that almost all electrophysiologically-classified dopaminergic neurons are tyrosine hydroxylasepositive (Brown et al, 2009), despite discrepancies found in some other studies (Margolis et al, 2006;Margolis et al, 2010). "Dopamine neurones" referred to in this study are therefore those that conform to electrophysiological and pharmacological criteria, but not necessarily to the content of dopamine.…”
Section: Vta Slice Preparation and Electrophysiological Recordingssupporting
confidence: 73%
“…If the I h current during a step from À50 to À100 mV was present, the neuron was considered a dopamine neuron; if not, the cell was classified as a GABA neuron. While the absence of I h reliably predicts that a VTA neuron is non-dopaminergic, I h is also present in a group of VTA neurons, which are not dopaminergic (Margolis et al, 2006).…”
Section: Electrophysiological Recordingmentioning
confidence: 92%
“…For example, the expression of I h current, resting membrane potential, spontaneous firing rate, and cell size are typical measures used to characterize DA neurons 2,7,8,16,17 . Using our method, it is also possible to characterize neurons based on their response to locally-applied nicotine or ACh 18,19 .…”
Section: Representative Resultsmentioning
confidence: 99%